Esophageal variceal ligation in the secondary prevention of variceal bleeding: Result of long term follow-up - Lahbabi, Mounia (The African Field Epidemiology Network, 2013)
INTRODUCTION: Long-term outcome of patients after band ligation have been poorly defined. Therefore, we conducted a long-term follow-up study to delineate the outcome of ligation in patients with portal hypertension in the Hassan II university hospital, Fes, Morocco. METHODS: Over 118 months patients treated by endoscopic variceal ligation were received regular follow- up and detailed clinical assessment of at least 24 months. RESULTS: One hundred twenty five patients were followed up for a mean of 31 months (range 12-107 months). Obliteration of the varices was achieved in 89.6 % (N = 112) of patients, with 3 +/-1.99 (range 1-8) endoscopy sessions over a period of 14 + /-6.8 weeks (range 3-28). The percentage of variceal recurrence during follow-up after ligation was 20.5 % (N = 23). Recurrence were observed in a mean of 22 months +/- 7.3 (range 3-48). Bleeding rate from recurrent varices was 30.4 % (7/23). Rebleeding from esophageal ulcers occurred in 5.6 % (7/125) of patients. Portal hypertensive gastropathy before and after eradication of varices was 17.6% (N = 22) and 44.6% (N = 50) respectively; p< 0.05. Fundal gastric varices was 30.4% (N = 38) and 35.7% (N = 40) before and after eradication of varices respectively; p> 0.05. The overall mortality was 4 % (N = 5). CONCLUSION: Band ligation was an effective technical approach for variceal obliteration with low rates of variceal recurrence, rebleeding and development of gastric varices. Furthermore, it was associated with frequent development of portal hypertensive gastropathy.